Hypothyroid Patients Encoding Combined MCT10 and DIO2 Gene Polymorphisms May Prefer L-T3 + L-T4 Combination Treatment – Data Using a Blind, Randomized, Clinical Study. Issue 3 (24th July 2017) - Carlé, Allan; Faber, Jens; Steffensen, Rudi; Laurberg, Peter; Nygaard, Birte
Abstract : Objectives: In previous studies, around half of all hypothyroid patients preferred levo-thyroxine (L-T4) + levo-triiodothyronine (L-T3) combination therapy, 25% preferred T4, and 25% had no preference. The reason for this is yet to be explored. Methods: A total of 45 overtly autoimmune, hypothyroid patients – now euthyroid on ≥6 months' L-T4 therapy – participated in a prospective, double-blind, cross-over study. The patients were randomized into 2 groups of either 3 continuous months' L-T4 therapy followed by 3 months' combination therapy or vice versa. In all periods, 50 μg L-T4 was blindly replaced by either (identical) 50 μg L-T4 or by 20 μg T3. L-T4 was hereafter adjusted to obtain normal serum TSH values. We investigated 3 single nucleotide polymorphisms (SNPs) on the type II iodothyronine deiodinase ( DIO2 ) gene (rs225014 (Thr92Ala), rs225015, and rs12885300 (ORFa-Gly3Asp)) and 1 SNP on the cellular membrane transport-facilitating monocarboxylate transporter ( MCT10 ) gene (rs17606253), and asked in which of the 2 treatment periods patients felt better (i.e., which treatment was preferred). Results: 27 out of 45 patients (60%) preferred the combination therapy. Two polymorphisms (rs225014 ( DIO2, Thr92Ala) and rs17606253 ( MCT10 )) were combined yielding 3 groups: none vs. 1 of 2 vs. both SNPs present, and 42 vs. 63 vs. 100% of our patients in the 3 groups preferred the combined treatment (Jongheere-Terpstra trend test, p = 0.009). Conclusion: The present study indicates that the combination of polymorphisms in DIO2 (rs225014) and MCT10 (rs17606253) enhances hypothyroid patients' preference for L-T4 + L-T3 replacement therapy. In the future, combination therapy may be restricted or may be even recommended to individuals harbouring certain polymorphisms.